Yosduan Ramos: 2017 Terri & Mark Lisagor Fellow
CSUCI Provost Dr. Geoff Chase; 2017 Terri & Mark Lisagor Fellow Yosduan Ramos; Dr. Margarita López-López Assistant Professor of Spanish; Julianne Gavino Lecturer of Art at 2017 SURF Program Reception.